2008
DOI: 10.1007/s00221-008-1578-3
|View full text |Cite
|
Sign up to set email alerts
|

Planning actions in autism

Abstract: It has been suggested that the deficit in understanding others' intention in autism depends on a malfunctioning of the mirror system. This malfunction could be due either to a deficit of the basic mirror mechanism or to a disorganization of chained action organization on which the mirror understanding of others' intention is based. Here we tested this last hypothesis investigating the kinematics of intentional actions. Children with autism and typically developing children (TD) were asked to execute two action… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

19
116
0
3

Year Published

2013
2013
2018
2018

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 163 publications
(138 citation statements)
references
References 16 publications
19
116
0
3
Order By: Relevance
“…Our results indicate that infants not only plan different action types differently, as shown for throwing versus placing by Claxton et al (2003), but also same actions with different degrees of difficulty, as shown for 7-year-olds by Fabbri-Destro et al (2009). In line with our first hypothesis that infants prepare for different degrees of difficulty by prospectively controlling their reaching speed, infants reached faster when the upcoming action was easier (vs. more difficult).…”
Section: Reachingsupporting
confidence: 83%
See 2 more Smart Citations
“…Our results indicate that infants not only plan different action types differently, as shown for throwing versus placing by Claxton et al (2003), but also same actions with different degrees of difficulty, as shown for 7-year-olds by Fabbri-Destro et al (2009). In line with our first hypothesis that infants prepare for different degrees of difficulty by prospectively controlling their reaching speed, infants reached faster when the upcoming action was easier (vs. more difficult).…”
Section: Reachingsupporting
confidence: 83%
“…It could be that infants plan differently for different types (or catego-ries) of actions and goal intentions (e.g., reaching with the intent to throw vs. place an object; here referred to as action type planning). Infants might also be able to plan their actions on a more fine-grained level, based on a continuous scale of task difficulty (here referred to as action difficulty planning), as shown for older children (Fabbri-Destro et al, 2009). In prior infant studies (Chen et al, 2010;Claxton et al, 2003) these two levels have been confounded.…”
Section: Discussion Study Imentioning
confidence: 99%
See 1 more Smart Citation
“…3) seems to be a promising way to tackle a range of neurodevelopmental and drugrelated disorders. In ASD, early motor cognition anomalies resulting in basic motor-understanding difficulties could be one of the crucial neurocognitive markers for ASD detection (Becchio, Pierno, Mari, Lusher, & Castiello, 2007;Cattaneo et al, 2007;Fabbri-Destro et al, 2009;Parma, Bulgheroni, Tirindelli, & Castiello, 2013;Rochat et al, 2013), and potentially they could be tested even in infancy, before the onset of unequivocal behavioral symptoms (for reviews from nonmotor perspectives, see Jones, Gliga, Bedford, Charman, & Johnson, 2014;Keehn, Müller, & Townsend, 2013;Klin, Shultz, & Jones, 2015). Furthermore, considering that ASD is a lifelong condition that usually requires permanent assistance, motor cognition anomalies may assume a pivotal role for setting (early) rehabilitative protocols to improve social functioning (Pineda, Carrasco, Datko, Pillen, & Schalles, 2014;Rogers et al, 2014;Zwaigenbaum, Bryson, & Garon, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Second, the research group of Rizzolatti has postulated that the primary deficit is not the responsiveness of the hMNS to the observation of others' actions, but the impaired organization of motor chains underlying the action representations (Cattaneo et al, 2007;Fabbri-Destro, Cattaneo, Boria, & Rizzolatti, 2009). They draw attention to the recent finding of action-constrained parietal mirror neurons in monkeys.…”
Section: The Visuomotor Map Hypothesismentioning
confidence: 99%